Cheese-flavored expanded snacks with low lipid content: Oil effects on the in vitro release of butyric acid and on the duration of the dominant sensations of the products. (May 2019) - Menis-Henrique, Michele Eliza Cortazzo; Janzantti, Natália Soares; Andriot, Isabelle; Sémon, Etienne; Berdeaux, Olivier; Schlich, Pascal; Conti-Silva, Ana Carolina
Abstract: With the aim of producing snacks with reduced lipid content, the effect of lipids on the in vitro release of butyric acid and on the duration of the dominant sensations of cheese-flavored expanded snacks were investigated. For that, snacks were obtained through pre-extrusion addition of aroma precursors of cheese to corn grits (butyric acid and cysteine) and sprinkled with sunflower oil in different proportions (6, 12, 18 and 24 g/100 g). The snack sprinkled with 6 g/100 g of sunflower oil showed higher release of butyric acid, compared to the other snacks with oil, when a chewing simulator was employed (simulation of aroma perception), and practically the same release in relation to the other snacks when the dynamic headspace of products was obtained (i.e. simulation of odor perception). All snacks with sunflower oil were described by the duration of salty taste, crunchy/crisp, cheese flavor, umami taste and oil flavor, indicating that the low use of sunflower oil (6 g/100 g) did not alter or prejudice the dominant sensations of the snacks. Therefore, the production of snacks with low addition of lipids is feasible, improving the nutritive value of these products that are so criticized because of the high lipid content. Highlights: Butyric acid and cysteine were used as aroma precursors in expanded snacks. The lower use of oil (6%) conferred better release of butyric acid measured in vitro. All snacks with oil (6, 12, 18 or 24%) were described by the same dominant sensations. Aroma precursors are an alternative for producing snacks with low lipid content.